2018
DOI: 10.1007/s00210-018-1591-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elastin-derived VGVAPG peptide on bidirectional interaction between peroxisome proliferator-activated receptor gamma (Pparγ) and beta-galactosidase (β-Gal) expression in mouse cortical astrocytes in vitro

Abstract: The process of degradation of the elastin-rich extracellular matrix produces elastin-derived peptides (EDPs). Different types of EDPs are detectable in the cerebrospinal fluid in healthy individuals and in patients after ischemic stroke. To date, it has been demonstrated that EDPs can regulate the development of insulin resistance in mice in a peroxisome proliferator-activated receptor gamma (Pparγ)-dependent manner. Therefore, the aim of this study was to investigate the impact of the elastin-derived valinegl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Because resistin is strictly controlled by PPARγ activation, our data allow to assume that VGVAPG peptide by interaction with this receptor can control resistin gene expression [88]. Interaction between PPARγ and VGVAPG has been proven in our previous study, in which VGVAPG peptide was shown to affect PPARγ expression and PPARγ-mediated effects in mouse astrocytes and SH-SY5Y cells [31,49]. As mentioned above, PPARγ is involved in resistin expression, which is strictly related to obesity and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Because resistin is strictly controlled by PPARγ activation, our data allow to assume that VGVAPG peptide by interaction with this receptor can control resistin gene expression [88]. Interaction between PPARγ and VGVAPG has been proven in our previous study, in which VGVAPG peptide was shown to affect PPARγ expression and PPARγ-mediated effects in mouse astrocytes and SH-SY5Y cells [31,49]. As mentioned above, PPARγ is involved in resistin expression, which is strictly related to obesity and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 55%
“…To date, previous studies have shown that EDPs and/or VGVAPG peptide increase the production and/or secretion inflammatory markers such as IL-1α, IL-1β, and IL-6 in ligamentum flavum cells, synovial cells, and melanoma cell lines [ 63 65 ]. On the other hand, our previous studies show that VGVAPG peptide increases the expression of PPARγ and decreases the expression of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and production of IL-1β in mouse astrocytes in a PPARγ-dependent manner, which suggest that the effect of VGVAPG is tissue dependent [ 31 , 66 ]. Interestingly, our latest study revealed that caspase-1 activity increases, which suggests that this caspase does not play an inflammatory role in mouse astrocytes [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of Pioglitazone was reversed by 10 nM of the VGVAPG peptide. Our previous research showed that 50 nM of the VGVAPG peptide decreased peroxisome proliferator-activated receptor gamma (Pparγ) expression caused by Pioglitazone and Rosiglitazone [ 34 ]. Such data suggest that VGVAPG activates molecular pathways that may then compete with other pathways activated by PPARγ agonists.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of Glb1 mRNA silencing with the use of 50 nM specific siRNA was verified by measuring the mRNA levels. Previously, knockdown of the Glb1 gene was estimated at 39% of the control mRNA and 60.05% of the control protein as described in [ 33 , 34 ]. In present manuscript knockdown of the Glb1 gene was estimated at 37.45% of the control mRNA (data not shown).…”
Section: Methodsmentioning
confidence: 99%